Answer:
b = 3, c = -2
Explanation:
Given the standard form of the expression with unknown value
6200.07 = 6.2 × 10^c + 7 × 10^d
Step 1:
We will write 6200.07 as a sum of whole number and a decimal.
6200.07 = 6200+0.07
Step 2:
Expressing each term in it standard form.
6200 = 6.2×10³ ((it has a positive power because it is a value greater than zero)
0.07 = 7×10^-2 (it has a negative power because it is less than zero)
6200.07 = 6.2 × 10^3 + 7 × 10^-2
Comparing with the question, it can be seen that b = 3, c = -2